Effect of clary sage oil as an aromatherapy on cardiac autonomic function among patients with premenstrual syndrome – A randomized controlled study. (June 2020) - Geethanjali, S.; Venugopal, V.; Poonguzhali, S.; Maheshkumar, K.
Abstract: Background: Premenstrual syndrome (PMS) is common among women in their reproductive age across the world and complementary therapies are being widely used in the management of PMS. Aromatherapy is one such complementary therapy and the objective of the current study is to evaluate its immediate effect on cardiac autonomic function among patients with PMS. Methodology: A total of 60 women with PMS were randomly allocated to either intervention group (clary sage aroma exposure; n = 30) or control group (water exposure; n = 30). Aroma exposure with aroma oil or water was given using aroma care diffuser. Short term HRV was measured at baseline and 10, and 20 min after inhalation. Results: Immediately after aroma exposure, the time domain parameters of short term HRV showed a significant (P < 0.05) improvement towards the parasympathetic dominance after the recovery phase. Frequency domain parameters also showed the same direction of changes. In contrast, control group subjects did not show any changes in the time and frequency domain parameters. Conclusion: The present study showed that inhalation of clary oil aromatherapy act as a potential therapeutic modality to improves the autonomic function towards vagal tone domination. Further studies with longer duration of aroma inhalations are required to warrant our finding. Highlights: Clary sage oil, in particular, is called a 'gift to the female' and has a restoring effect in premenstrual syndrome (PMS). This is the first study to report the immediate neurophysiological effect of clary sage oil inhalation in patients with PMS. Inhalation of clary oil aromatherapy act as a potential therapeutic modality to improves the autonomic function among the patients with PMS.